2022
DOI: 10.2196/29745
|View full text |Cite
|
Sign up to set email alerts
|

Remote Psychological Interventions for Fear of Cancer Recurrence: Scoping Review

Abstract: Background Patients with cancer and survivors may experience the fear of cancer recurrence (FCR), a preoccupation with the progression or recurrence of cancer. During the spread of COVID-19 in 2019, patients and survivors experienced increased levels of FCR. Hence, there is a greater need to identify effective evidence-based treatments to help people cope with FCR. Remotely delivered interventions might provide a valuable means to address FCR in patients with cancer. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…Moreover, breast and prostate cancers belong to those types of cancers where caregivers' involvement can be necessary, since some decisions for therapies also involve the sphere of intimacy and fertility (Northouse et al, 2007 ; Dorros et al, 2010 ). In these cases, partners ideally play a fundamental role in making decisions, insofar as the decision has an impact on them as well (Segrin and Badger, 2010 ; Muzzatti et al, 2020 ; Cincidda et al, 2022 ). For this reason, the promotion of specific interventions to support dyads facing the diagnosis of breast or prostate cancer becomes even more crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, breast and prostate cancers belong to those types of cancers where caregivers' involvement can be necessary, since some decisions for therapies also involve the sphere of intimacy and fertility (Northouse et al, 2007 ; Dorros et al, 2010 ). In these cases, partners ideally play a fundamental role in making decisions, insofar as the decision has an impact on them as well (Segrin and Badger, 2010 ; Muzzatti et al, 2020 ; Cincidda et al, 2022 ). For this reason, the promotion of specific interventions to support dyads facing the diagnosis of breast or prostate cancer becomes even more crucial.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we (1) found significant differences in FCR levels from the time of first diagnosis of malignancy to 2 months after discharge in newly diagnosed cancer patients; (2) demonstrated a trend of increasing and then decreasing FCR levels in patients over the course of three measurements; (3) showed that the junior secondary and less education level, rural residence, advanced tumor and high EA level were risk factors for higher FCR. This implies that without early psychological intervention, patients may face relatively serious negative emotional distress 29 …”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, treatments for psychological symptoms of cancer, that is, those impacting patients' emotional health (e.g., anxiety), have been delivered face-to-face and shown to improve psychological wellbeing. [3][4][5] However, numerous barriers reduce their accessibility including the logistics of attending appointments, physical symptoms (e.g., pain, limited mobility), lack of family support, financial issues, perceived stigma, and limited health professional availability in rural/remote areas. [6][7][8][9] Digital interventions, defined as programs that provide information and support for physical and/or mental health problems via a digital platform, 10 may overcome these barriers, as they allow patients to complete treatment remotely and anonymously, 3 thereby reducing healthcare system burden.…”
Section: Introductionmentioning
confidence: 99%
“…7 When successfully implemented, digital interventions offer scalability, improved patient selfmanagement, care continuity, reduced healthcare costs, and reduced resource expenditure. 3,11 Consequently, psychological interventions are being adapted for internet delivery (e.g., the iConquerFear intervention) 12 to meet cancer survivors' changing needs.…”
Section: Introductionmentioning
confidence: 99%